Severe acute respiratory syndrome coronavirus 2 and influenza A virus co-infection in a nine-year-old boy from a family cluster – case report - Tomasik, Anna; Pokorska-Śpiewak, Maria; Talarek, Ewa; Marczyńska, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2020)
In this case report we present a nine-year-old boy from a family cluster with SARS-CoV-2 and influenza virus co-infection. He presented with the most common manifestations of COVID-19 reported in paediatric population – fever and cough. Severe acute respiratory syndrome coronavirus 2 infection was diagnosed by RT-PCR assay, and influenza type A by rapid immunochromatic assay testing. The course of disease was mild, despite co-infection with two viruses. In the time of COVID-19 pandemic testing for influenza, respiratory syncytial virus (RSV), and SARS-CoV-2 in suspected cases is essential for establishing a diagnosis, and it has important implications for patient management.